إعداد خرائط الغمر لحوض نهر الكبير الشمالي نتيجة انهيار مفترض لسد16تشرين - عبد الرحمن عباس; خليل راما (Latakia University Journal -Engineering Sciences Series, 2017)
آلاف السدود تم بناؤها حول العالم،إلا أن تاريخ بنائها مقترن مع تاريخ حافل من حالات الفشل والانهيار، نظراً لارتفاع مناسيب المياه فيها، مما يعود بعواقب كارثية على البيئة والمجتمع، فعندما يفشل السد تتحرر كميات كبيرة جداً من المياه مهددةً حياة الأشخاص وممتلكاتهم، ويعود هذا إلى الوقت القصير المتاح للتحذير والإخلاء. يوفر هذا البحث لمحة عن أهم أسباب الانهيار، مع دراسة لاحتمال الفشل الناتج عن خرق افتراضي في سد 16 تشرين ناتج عن تدفق الماء من فوق قمته، حيث تم التنبؤ بالخرق المؤدي للانهيار وتحديد خصائصه وهي: ارتفاع الخرق، عرض الخرق، الزمن اللازم لتطور الخرق، التدفق الأعظمي الخارج منه، ومن ثموضع خرائط الغمر التي تمثل حدود انتشار الموجه الفيضانية في المجرى، كما تم اقتراح خطة مبسطه للإخلاء. وتوصلت النتائج إلى أن الموجة الفيضانية الناتجة عن الانهيار تندفع محملة بغزارة 54631 مشكلة جدار مائي بارتفاع 17 متر ينتقل عبر المجرى بسرعة14 m/secوينتشر على مساحة 45.22 كيلومتر مربع،مسبباّ غمر 7 قرى أهمها ستخيرس وروضو اللتان تغمران بالكامل، و 30 منشأة اقتصادية أهمها المنطقة الصناعية التي تغمر بالكامل أيضاّ،وتراوحت أعماق الغمر من m 17-2 ،مما يسبب خسائر فادحة ويلحق الضرر بحوالي 30000 شخص وأكثر من 7000 شخص من المتوقع أن يلقوا حتفهم مالم يتم الإعداد الفعلي لخطة طوارئ. Thousands of dams have been built around the world, but, the date of construction is associated with a history of failures and collapse, due to the high water levels, generating higher returns consequences disastrous for the environment and society, when dam fails released very large amounts of water threatened the lives of persons and property, it returns to the short time available for warning and evacuation. This paper provides an overview of the most important reasons for the collapse, with a study about possibility failure product from supposed breach in 16 Tishreen dam, caused by the flow of water over the top, where the predicted of breach that leading to collapse is done and determine its characteristics, namely: High, width, time required to development of the breach, the maximum flow out of it, and also generate flood maps that represent the limits of the spread of flood wave downstream, in addition tosuggest a simplified plan for the evacuation Results led to the flooded wave caused by the collapsehurtling loaded adischargeabout 54631 , causes a wall of water with 17 meters high moves through the downstream river with 14 m/sec speed, the wave spreadover 45.24 ,causing submerge for 7 villages the most important of it Stkhers and Rodo which are completely submerged, and 30 economical facility the most important of it industrial area that also completely submerged, the water depths ranged from 2 to 17 meter, which causing heavy casualtiesand damage about 30000 people, and more than 7000peopleare expected to die, unless the actual preparations of emergency plan.